Kaposi’s Sarcoma in Film - Richard F. WAGNER; Alex C. HOLLIDAY (Revista de Medicina y Cine / Journal of Medicine and Movies, 2016)
Kaposi’s sarcoma, a historically rare, indolent cutaneous malignancy of elderly men emerged as a frequent and easily recognizable cutaneous manifestation of Acquired Immunodeficiency Syndrome in the 1980s. Since these tumors were often visible to the public, Kaposi’s sarcoma quickly became a stigmatizing marker for those infected, and predicted the high mortality risk from comorbid opportunistic infections. English language films released from 1985-2008 are analyzed for their depictions of Kaposi’s sarcoma, and the role(s) it played in these films. With the advent of highly active antiretroviral therapy for those with HIV infection, Kaposi’s sarcoma has once again become relatively rare.